An Analysis of User Complaints on Chat Reference during the COVID-19 Pandemic: Insights into User Priorities. - Barrett, Kathryn; Crichton, Chad; Logan, Judith (Internet Reference Services Quarterly)
This study aims to identify patterns in user complaints within chat transcripts before and during the COVID-19 pandemic. The researchers analyzed 3,339 chat transcripts from an academic chat reference consortium between January 2019 to December 2021. Transcripts were hand-coded for pandemic status, semester, user type, presence of a complaint, complaint type and subtype, and complaint resolution. We tested the significance of relationships between variables using Pearson's chi-square test of independence and Fisher's exact test. Over the three-year study period, 17.6% of chats contained at least one complaint, with faculty and graduate students complaining more than expected, and undergraduates complaining less than expected. The most common complaint types concerned e-resources, accounts, and research. There were significant differences in complaints according to user type: students and faculty complained more about e-resources, staff and alumni complained more about accounts, and members of the public complained more about policies. The researchers found a statistically significant increase in complaints during the pandemic, with more complaints about document delivery and borrowing and e-access eligibility than expected, and fewer complaints about library accounts and noise than expected. Most complaints across the study period were resolved, typically via referral.